Population pharmacokinetic modeling of sustained release lithium in the serum, erythrocytes and urine of patients with bipolar disorder. - Couffignal, C.; Bertrand, J.; Sportiche, S.; Jarroir, Marine; El Balkhi, S.; Djebrani-Oussedik, N.; Poupon, J.; Declèves, X.; Mentré, F.; Bellivier, F. (European Journal of Clinical Pharmacology, 2019)
Purpose: Lithium (Li), the first-line treatment of bipolar disorder, was first developed as an immediate-release form with a routine therapeutic drug monitoring 12 h after the last dose. In Europe, the most commonly prescribed form is a sustained release (srLi). Yet no pharmacokinetics (PK) study has been published of srLi, administered once a day, in adults. The present study describes srLi PK in the serum and erythrocytes of bipolar patients.Methods: To assess srLi PK, we studied prospectively 17 French bipolar patients on a median dose of 1000 mg (600-1600) for at least 2 years. Serum (S), erythrocyte (E) concentrations, and urinary (U) amount were collected over 8 h after 15 days of morning intake using monitoring electronic medical system (MEMs). Population PK parameters were estimated using the SAEM algorithm (MONOLIX 4.3.3 software).Results: Using a population approach, we built a PK population model of srLi including one S compartment (VS = 23.0 L, ClS = 1.21 L h−1), one E compartment (VE = 64.7 L, ClSE = 3.63 L h−1, ClES = 9.46 L h−1), and one U compartment (F = 0.62) and estimate the ratio of concentrations to Li in E over S at 0.38 with 27% between-subject variability.Conclusion: This is a PK model of srLi once a day in bipolar patients using a population approach simultaneously describing Li concentrations in serum, erythrocytes, and urine which provide an estimate of the ratio of concentration in erythrocyte over serum and its between-subject variability (BSV).